Adoption of Prefabrication in Small Scale Construction Projects - Shabir Hussain Khahro; Nafees Ahmed Memon; Tauha Hussain Ali; Zubair Ahmed Memon (Civil Engineering Journal, 2019)
The construction industry is facing numerous difficulties in managing construction waste, quality, environment, permanence, safety, and greater construction cost. Dynamic change is needed today to overcome new challenges in the construction industry. Adoption of prefabrication is one of the possible solutions to such problems. This paper explores the advantages in prefabrication adoption with its possible disadvantages (barriers) through the qualitative study. This paper is an addition to the existing literature of prefabrication specially for developing countries where the acceptance rate of new approaches is difficult. It covers private residential project and a public housing project. This study also aims to evaluate the current status of prefabrication adoption in small-scale construction projects. A set of the questionnaire is used to collect the data and Average Index (AI) method using SPSS has been used to analyze the results. Shorter construction time, Low site waste and better supervision are the main advantages. Higher initial construction cost and Strict & difficult design changes are the key disadvantages. It is analyzed that the conventional construction method is more frequently used when compared with prefabrication concept.